Twice in a lifetime eaudiobook - Baron, Melissa (Dreamscape Media, 2022)
Isla has fled the city for small-town Missouri in the wake of a painful and exhausting year. With her chronic anxiety at a fever pitch, the last thing she expects is to meet a genuine romantic prospect. And she doesn't, but she does get a text from a man who seems to think he's her husband. Obviously, a wrong number—except, when she points this out, the mystery texter sends back a picture of them, on their wedding day. Isla cautiously starts up a texting relationship with her maybe-hoax, maybe-husband Ewan, who claims to be reaching out from a few years into the future. Ewan knows Isla incredibly well and seems to love her exactly as she is, which she can hardly fathom. But he's also grieving, because in the future, he and Isla are no longer together. Ewan is texting back through time to save her from a fate he won't share with her; all she can do to prevent that fate is to learn to be happy, now, in the body she has, with the mind she has. The only trouble is the steps she takes in that direction might be steps away from a future with Ewan. Melissa Baron's time-crossed romance features a quintessentially endearing and brave protagonist and an engrossing plot that will keep you listening until its breathtaking finish.